Evaluation of Antifungal Effect of Alcoholic Extract of Achillea Millefolium and Trachyspermum ammi Against Candida albicans Isolated from Denture Stomatitis - Nazli Ebrahim Netaj; Maryam Rezaei Dastjerdi; Saham Ansari; Kamran Amirian Chayjan; Mahdi Sepidarkish; Jalal Jafarzadeh; Akbar Hossein Nejad; Mojtaba Taghizadeh Armaki (Tehran University of Medical Sciences, 2022)
Background and Aim: Denture stomatitis is the most prevalent oral mucosal lesion among denture wearers. Because there have been multiple reports of resistance of Candida species to antifungal drugs in the last two decades, if the antifungal properties of Achillea millefolium and Trachyspermum ammi are validated, these compounds may be a suitable adjuvant drug along with the use of common antifungal drugs. Therefore, the current study aimed to assess the antifungal activity of alcoholic extracts of Achillea millefolium and Trachyspermum ammi against Candida albicans isolated from denture stomatitis. Materials and Methods: Antifungal sensitivity of 50 isolates of C. albicans with the origin of denture stomatitis to the alcoholic extracts of Achillea millefolium and Trachyspermum ammi plants as well as the antifungal drugs miconazole and nystatin was determined by broth microdilution method and according to CLSI-M27S4 guidelines. The range of dilution for all compounds was 0.016-16 μg/ml. A concentration of compounds that showed at least 50% growth inhibition as compared to the positive control group was considered MIC (minimum growth inhibitory concentration). Statistical analysis was done using SPSS software and the significance level was considered as P<0.05. Results: The MIC ranges in microbroth dilution method for the antifungal drugs miconazole, nystatin, as well as the alcoholic extracts of Achillea millefolium and Trachyspermum ammi plants on C. albicans, were close to each other, indicating that their effectiveness against C. albicans species does not differ significantly (P<0.05). The Achillea millefolium methanolic extract had the highest and lowest MIC values, with an average of 2.67±2.55 μg/ml and 0.067±0.057 μg/ml, respectively. A significant difference (P<0.001) was observed when the MICs outcomes the herbal alcoholic extracts and antifungal drugs were compared. Conclusion: Based on the obtained MICs, Achillea millefolium and Trachyspermum ammi alcoholic plant extracts have a lesser efficacy than the antifungal drugs, but even though they may have a lower MIC and more effectiveness than other chemical drugs.